Book review - Ballance, Virginia C. F. (International Journal of Bahamian Studies, 2008)
Breaking the Glass Ceiling: the Stories of Three Caribbean Nurses by Jocelyn Hezekiah. (University of the West Indies Press, 2000). Trailblazers in Nursing Education: a Caribbean Perspective by Hermi Hyacinth Hewitt (Canoe Press, 2002).